Mechanistic insights into flavor deterioration in bitter sturgeon caviar: Evidence from lipidomics and metagenomics - Guixin Han; Ke Li; Jinlin Wang; Peng Xu; Tianhong Liu; Xinxing Xu; Yuanhui Zhao (Food Research International, 2026)

Dynamic flavor perception in sturgeon caviar during oral processing revealed by volatile release, neural responses, and phospholipid changes - Guixin Han; Ke Li; Jinlin Wang; Peng Xu; Tianhong Liu; Ruichang Gao; Lianfa Gong; Xing Zhao; Xinxing Xu; Yuanhui Zhao (Food Chemistry, 2026)

Effects of Offshore Wind Farm-Associated Electromagnetic Fields on the Physiology and Behavior of Sebastes schlegelii - Tingting Wen; Hongwu Cui; Zhengguo Cui; Xinxing Zhang; Qi Zhang; Juanjuan Sui; Xixi Han; Huanhuan Jiang; Congcong Xing; Mian Xie; Yanrong Zhou; Weihan Yin; et al. (Fishes, 2026)
To evaluate the potential biological effects of electromagnetic fields from offshore wind farms on Sebastes schlegelii, a laboratory-controlled chronic exposure experiment was conducted using a magnet-based static magnetic field system. Each group contained 60 fish distributed across four replicate tanks, with 15 fish per tank, and the fish were continuously exposed for 20 d under controlled water-quality conditions. Daily video monitoring of collective shoaling behavior was combined with multi-tissue physiological and biochemical analyses. Electromagnetic field exposure increased the swimming speed, burst frequency, activity ratio, spatial coverage, occupancy entropy, and polarization, while reducing the nearest neighbor distance, group radius, and group area. At the physiological level, cortisol increased mainly in the liver and brain, ACTH showed tissue-dependent modulation, SOD remained relatively stable, and glutathione increased in multiple tissues, especially in the liver, gut, and brain. Correlation analysis indicated a close coupling between behavioral reorganization and endocrine–redox regulation, suggesting that chronic EMF exposure shifted Sebastes schlegelii into a stress-associated but functionally coordinated collective state.

Lipid-derived bitter compounds in sturgeon caviar: Metabolomic identification and sensory validation - Guixin Han; Yanqin Liu; Ke Li; Jinlin Wang; Fan Bai; Peng Xu; Tianhong Liu; Jian Li; Xinxing Xu; Yuanhui Zhao (Food Chemistry, 2026)

Evaluating urban nighttime lighting and perceived safety in residential areas: An empirical investigation in Xi’an City - Chengwei Liu; Ling Liu; Xinxing Wang; Beilei Han; Leyi Chen (Building and Environment, 2026)

Deep Subdomain Adaptation Network for Three-Dimensional Mineral Prospectivity Modeling with Imbalanced Data: A Case Study of the Damiao–Hongshila Fe–V–Ti Belt, China - Zhiqiang Zhang; Wenliang Chen; Emmanuel John M. Carranza; Wei Han; Xinxing Liu; Yingjie Li; Juan Zhang; Feng Li; Ziyang Lu; Yongjun Su; Gongwen Wang (Natural Resources Research, 2026)

Effect of pulsed light treatment on 4 °C refrigerated Atlantic salmon (Salmo salar) quality: Shelf life, microbial community changes, and antimicrobial mechanisms - Guixin Han; Yiyi Wang; Ke Li; Tianhong Liu; Lianfa Gong; Wentao Liu; Xinxing Xu; Yuanhui Zhao (Food Control, 2025)

Hydrogen bond network suppresses cascade degradation for high-performance air-processed perovskite solar cells - Xinxing Liu; Xiao Han; Yue Yu; Dongmei He; Jianhong Yi; Jiangzhao Chen (Chemical Engineering Journal, 2025)

Boosting solar hydrogen generation by growth of UiO-based MOF on metal sulfide surface - Zhiyun Dong; Du Li; Tao Han; Xueli Zhao; Xinxing Lei (Journal of Environmental Chemical Engineering, 2025)

Flavor formation mechanisms based on phospholipid fermentation simulation system in oyster juice co-fermented by Lactiplantibacillus plantarum and Saccharomyces cerevisiae - Ke Li; Guixin Han; Li Liu; Yuanhui Zhao; Tianhong Liu; Hongjiang Wang; Xinxing Xu (Food Chemistry, 2025)

Deep neural network and transfer learning for annual wetland vegetation mapping using sentinel-2 time-series data in the heterogeneous lake floodplain environment - Jinquan Ai; Xinxing Han; Lijuan Chen; Haiqing He; Xiaolong Li; Yongbin Tan; Tianci Xie; Xintao Tang (International Journal of Remote Sensing, 2025)

Hypoglycemic peptide preparation from Bacillus subtilis fermented with Pyropia: Identification, molecular docking, and in vivo confirmation - Guixin Han; Yuxian Xu; Jiayu Li; Ke Li; Xinxing Xu; Xin Gao; Yuanhui Zhao; Hong Jiang; Xiangzhao Mao (Food Chemistry, 2025)

Minimizing interfacial energy losses via fluorination strategy toward high-performance air-fabricated perovskite solar cells - Xiao Han; Xinxing Liu; Yue Yu; Dongmei He; Jing Feng; Jianhong Yi; Jiangzhao Chen (Chemical Engineering Journal, 2024)

Enhanced therapeutic potential of Flotillins-modified MenSCs by improve the survival, proliferation and migration - Fangfang Cheng; Longkai Ji; Pan Li; Zhisheng Han; Yanan He; Fen Yang; Zhihao Xu; Yonghai Li; Tao Ruan; Xinxing Zhu; Juntang Lin (Molecular Biology Reports, 2024)

Revealing the long-term impacts of plant invasion and reclamation on native saltmarsh vegetation in the Yangtze River estuary using multi-source time series remote sensing data - Jinquan Ai; Lijuan Chen; Haiqing He; Xinxing Han (Ecological Engineering, 2024)

Geochronology and petrogenesis of the Yeba formation volcanic rocks in the Epingsong area, southern Lhasa terrane, Tibet: record of the Neo-Tethys subduction - Peng Fan; Bin Zhou; Aihua Xi; Xinxing Qiao; Liang Pan; Kui Han; Xu Chao; Wenbo Yang; Zhongshan Wu (International Geology Review, 2023)

Miocene adakitic volcanism in eastern Lhasa Terrane, Tibet: perspective from zircon U–Pb geochronology, whole-rock geochemistry and Sr–Nd–Hf isotopes - Bin Zhou; Kui Han; Chaoming Xie; Weipeng Zhu; Liang Pan; Xinxing Qiao; Zhongcheng Zeng; Chunkit Lai; Peng Fan (International Geology Review, 2022)

MAP3K2 augments Th1 cell differentiation via IL-18 to promote T cell-mediated colitis - Ningbo Wu; Dongping Chen; Hongxiang Sun; Jianmei Tan; Yao Zhang; Tianyu Zhang; Yuheng Han; Hongzhi Liu; Xinxing Ouyang; Xiao-Dong Yang; Xiaoyin Niu; Jie Zhong; et al. (Science China Life Sciences, 2021)

An efficient callus suspension culture system for triploid bermudagrass (Cynodon transvaalensis × C. dactylon) and somaclonal variations - Shaoyun Lu; Zhongcheng Wang; Xinxing Peng; Zhenfei Guo; Gengyun Zhang; Liebao Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)